THE ROLE OF CARTOONS IN TEACHING A FOREIGN LANGUAGE IN PRESCHOOL EDUCATION (Archive of Conferences, 2022)
In this article, we would like to demonstrate the old and modern methods of teaching a foreign language in preschool educational institutions. The article discusses innovative methods of teaching foreign languages and various methods used in the course.